308. Identification of Prosthetic Hip and Knee Joint Infections in Administrative Databases. (26th November 2018) - Kandel, Christopher; Davey, J Roderick; Daneman, Nick; McGeer, Allison
Abstract: Background: Canada lacks a prosthetic hip and knee joint infection (PJI) registry, leaving active surveillance to be orchestrated by individual hospitals, which is limited by cost and narrow scope. Administrative databases are potentially an ideal instrument for infection surveillance, but detection algorithms relying solely on PJI diagnostic codes alone have been hampered by low specificity. There is a need to develop improved strategies to efficiently and accurately identify PJIs using health administrative databases. Methods: Combinations of International Classification of Disease, Tenth Revision, diagnostic and procedure codes were used to create testing cohorts among individuals treated at two institutions in Toronto, Ontario, from April 1, 2015 until March 31, 2016. These cohorts were compared with a reference standard of PJIs, which were identified by chart reviews of every individual who underwent a hip or knee revision operation at these institutions during the study period. The primary outcomes were the performance characteristics of each algorithm. Results: Over the 1-year study period, there were 471 revision operations for 405 patients, of which 155 (33%) were performed for the treatment of a PJI. Of the 405 individuals, 108 (27%) had a PJI as the surgical indication; there were 57 (53%) two-stage procedures, nine (8%) single-stage procedures, 34 (31%) incision and drainage procedures with implant retention, and eight (7%) excisional arthroplasties. The combination of a revision operation code plus a PJI diagnosis code was the most robust detection method: sensitivity 0.86 (95% confidence interval, 0.79–0.91) and specificity 0.99 (0.98–1.00). Coupling codes for a revision operation and insertion of a peripherally inserted central catheter yielded a sensitivity of 0.45 (0.37–0.53) and specificity of 1.00 (0.98–1.00). PJI codes alone had a sensitivity of 1.00 (0.86–1.00) and specificity 0.50 (0.23–0.77). Conclusion: The combination of a revision operation procedure code and a PJI diagnosis code is sensitive and specific for the detection of a PJI in administrative databases. This is a promising avenue for national PJI surveillance and has the potential to facilitate future research in the prevention and management of PJIs. Disclosures: All authors: No reported disclosures.